2020
DOI: 10.1002/jmri.27193
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Surface‐Based Analysis of Cartilage MRI Data in Knee Osteoarthritis: Validation and Initial Clinical Application

Abstract: Background Traditional quantitative analysis of cartilage with MRI averages measurements (eg, thickness) across regions‐of‐interest (ROIs) which may reduce responsiveness. Purpose To validate and describe clinical application of a semiautomated surface‐based method for analyzing cartilage relaxation times (“composition”) and morphology on MRI, 3D cartilage surface mapping (3D‐CaSM). Study Type Validation study in cadaveric knees and prospective observational (cohort) study in human participants. Population Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…A 3D surface analysis provides the possibility of spatially localizing the deformational and compositional effects of joint-loading on articular cartilage and could also assist in determining the regions most prone to exhibit cartilage degeneration. 29…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 3D surface analysis provides the possibility of spatially localizing the deformational and compositional effects of joint-loading on articular cartilage and could also assist in determining the regions most prone to exhibit cartilage degeneration. 29…”
Section: Discussionmentioning
confidence: 99%
“…As the disease‐induced compositional changes in cartilage reflected in T 1ρ and T 2 measurements can be of the same order, and appear in similar cartilage regions, as exercise‐induced changes, it is important to mitigate these effects when conducting clinical OA trials. A 3D surface analysis provides the possibility of spatially localizing the deformational and compositional effects of joint‐loading on articular cartilage and could also assist in determining the regions most prone to exhibit cartilage degeneration 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subject cohort used in this cross-sectional study has previously been described in a study assessing longitudinal changes in cartilage morphology and composition [ 12 ]. Between April 2017 and June 2018, 15 patients with knee OA were recruited from specialist orthopaedic knee clinics at a University teaching hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative MRI may also be helpful in such studies looking at understanding and monitoring the biological changes that occur in ligaments post augmentation or repair. Newer techniques have used 3D cartilage surface mapping to analyse these cartilage changes [ 12 ]. Furthermore, Prasad et al used a longitudinal approach and found that T1rho and T2 measurements may predict progression of knee OA, in particular degenerative cartilage abnormalities [ 13 ].…”
Section: Introductionmentioning
confidence: 99%